Design (non) fiction : deconstructing/reconstructing the definitional dualism of A - Franziska, Pilling (2021)
A Space Odyssey (Kubrick, 1968) speculates on humanities technological ascension through the exploration of space and the ultimate transcendence of humanity galvanised by the invention of AI. Every detail of this portrayal was an exercise in World Building, with careful considerations of then state-of-the-art technology and informed predictions. Kubrick’s speculative vision is comparative to the practice of Design Fiction, by suspending disbelief and leveraging a technologies emergence to question the future’s sociotechnical landscape and its ramifications critically. Discovery’s AI system, Hal9000, is a convincing speculation of intelligence with Kubrick’s vision showcasing current and long-term aims in AI research. To this end, Hal9000 uniquely portrays Artificial General Intelligence (AGI) underpinned by visualising ‘narrow’ AI subproblems; thereby, simultaneously highlighting then current research agendas within AI and manifesting them into the aspirational research agenda of human-computer symbiosis. As a result of Kubrick’s mastery in suspending a viewer’s disbelief despite portraying a particular reality for AI, and humanities fascination with artificial life, the term AI simultaneously refers to the grand vision of AGI as well as relating to the contemporary reality of narrow AI. This confusion, along with establishing AI’s ontology, are current challenges that need addressing to create effective and acceptable realisations of AI. This paper responds to the ontological confusion by reviewing and comparing Kubrick’s speculative methodology to the practice of Design Fiction by unpacking Hal9000 as a diegetic prototype while defining the active threads of ‘AI’s Definitional Dualism’. The paper will also present a Design Fiction submerged in the reality of narrow AI and the adoption of a More-Than Human Centred Design approach to address the complexity of AI’s ontology in alternative ways. Finally, this paper will also define the importance of researching the semantics of AI technology and how film and Design Fiction offer a discursive space for design research to transpire.